2020
DOI: 10.1057/s41291-020-00138-8
|View full text |Cite
|
Sign up to set email alerts
|

How the configurations of job autonomy, work–family interference, and demographics boost job satisfaction: an empirical study using fsQCA

Abstract: In the gig economy era, job characteristics that affect employees' job satisfaction have undergone significant changes. However, this has not been studied adequately in the context of Asia. This study applies the job demand-resource model to understand the effect of job autonomy and work-family interference on the job satisfaction of full-time and part-time employees in China, while considering the role of demographics. A total of 415 respondents were analyzed through fuzzy set qualitative comparative analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Job autonomy is the permitted extent of independence and discretion when performing professional tasks [ 22 ], including time and scheduling, and this is a key determinant of job satisfaction [ 72 ]. A majority of existing studies explain the relationship between employee JA and EJS in terms of JD-R theory and the resource-based view.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Job autonomy is the permitted extent of independence and discretion when performing professional tasks [ 22 ], including time and scheduling, and this is a key determinant of job satisfaction [ 72 ]. A majority of existing studies explain the relationship between employee JA and EJS in terms of JD-R theory and the resource-based view.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Job satisfaction is a pleasant emotional state resulting from evaluating one's job and an affective reaction to one's job and an attitude toward one's job. Increased job satisfaction is linked to better performance, improved stress-coping, high job engagement, lower absenteeism, structural enrichment, lower workplace incivility, job autonomy, organizational citizenship behavior and employee retention (Côt e et al, 2021;Li et al, 2019;Koon and Pub, 2018;Wu and Zhou, 2020;Zhang et al, 2019). Job satisfaction directly relates to job motivation, and increased job satisfaction and job motivation enhance the positive perception of employees on work-life balance (Palumbo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…4,[37][38][39] Previous studies on this subject have shown not only that negative effects of working hours are lower in countries with a lower level of welfare but also that work autonomy is the only key factor in those with a higher level of welfare. 4,[40][41][42][43] Only when there is a difference between actual and desired working hours, however, the length of working hours is more associated with satisfaction with work environment as compared with work characteristics. 4,37,44 In this regard, studies have also examined effects of the length of hours on satisfaction with work environment considering multiple factors, such as job complexity and control over working hours.…”
Section: Discussionmentioning
confidence: 99%